As decisões de investimento na Fundação Hospitalar de Minas Gerais e seus reflexos nos indicadores de qualidade - Sandra Rosaria Alvares da Silva (2008)
In Brazil the State performs an important function of allocation of financial resources. Among the many services it offers, Health stands out. Its quality depends not only on investments but also on a responsible and efficient public management, aimed at results. This work has the objective of investigating, within a chain of public hospitals, FundaçãoHospitalar do Estado de Minas Gerais (FHEMIG), how the resources avaiable in the budget are spent, so that better results are granted to the population, as well as the impact of those results as measured by hospital indicators. The public budget has an outstanding approach,since its managers should abide to the laws that regulate the use of its correpondent financial resources. Several investments were made so as to enable the Fundação in assisting more people with quality, translated into enlargements, equipment, information technology, human resource training, and scientific research. Some procedures were adopted aiming at optimizing the resources, such as stock control and introduction of clinical protocols. Better results were shown during that period, such as those measured by the rates of therapeutic efficiency and hospital occupation. Nevertheless, the rate of patients' return increased and no reduction was shown in the rate of mortality. Presence of other factors interfering with the assistance quality, such as medical care, could be noticed. Hospital indicators are valuable tools for monitoring hospital assistance quality, by means of which it is possible to objectively assess if there was improvement, stability or worsening of it. The quantity analysis of indicator variations is not sufficient for inferring about the hospital performance, but it acts as an alert for investigations to be performed in site. An increase in mortality rate, for instance, may be related both with the hospital inefficiency or to the increase on the number of patients in irreversible clinic situations. Nevertheless, the increase or the occurrence of abnormal high indexes for longer periods suggests problems within the hospitals. In relation to the use of the budget by FHEMIG, it was observed that the Fundação budget is adapted to meet its goals, and not only as a mere tool for expenditure control. Within the budget, resources may be relocated from an investment to another, upon due justification and approval of the board of directors. To promote the investments, resources from the Treasury of the State of Minas Gerais were used, since resources from SUS refer, basically, to payment of services rendered to its users. According to what was observed in this work, to obtain better results in assisting the population, several investments are necessary, besides the adoption of procedures capable of better control of expenditure. Another important conclusion is the necessity of monitoring the service by means of hospital indicators which were shown as an important management tool within the research organization. Therefore, a satisfactory assessment, by means of hospitalindicators, is related to a positive management of the budget resources.